2020
DOI: 10.2516/ogst/2020025
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical stability analysis of mixed finite element model of shale-gas flow with geomechanical effect

Abstract: In this work, we introduce a theoretical foundation of the stability analysis of the mixed finite element solution to the problem of shale-gas transport in fractured porous media with geomechanical effects. The differential system was solved numerically by the Mixed Finite Element Method (MFEM). The results include seven lemmas and a theorem with rigorous mathematical proofs. The stability analysis presents the boundedness condition of the MFE solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The results indicated that the gas effective permeability increases in a less complex and more discrete pore network. El-Amin et al [10] introduced a theoretical foundation of the stability analysis of the mixed finite element solution to the problem of shale-gas transport in fractured porous media with geomechanical effects, in which the differential system was solved by the Mixed Finite Element Method (MFEM).…”
Section: Accepted: 22 February 2021mentioning
confidence: 99%
“…The results indicated that the gas effective permeability increases in a less complex and more discrete pore network. El-Amin et al [10] introduced a theoretical foundation of the stability analysis of the mixed finite element solution to the problem of shale-gas transport in fractured porous media with geomechanical effects, in which the differential system was solved by the Mixed Finite Element Method (MFEM).…”
Section: Accepted: 22 February 2021mentioning
confidence: 99%